Prevalensi Kusta Pausibasiler Dan Multibasiler Berdasarkan Karakteristik Kepadatan Hunian, Riwayat Kontak, Sosial Ekonomi Di Kabupaten Belu Provinsi Nusa Tenggara Timur - Fahik, Alexander; Wahjoedi, Imam; Supardi, FX. Supardi (STIKES Wira Husada Yogyakarta, 2014)
Background: Leprosy, a tropical diseases are still a health problem in the world. Distribution of leprosy at 2007 were 61 cases, in 2008, 33 cases, 2009 were 30 cases, 30 cases in 2010, 25 cases at 2011 and 2012 as many as 25 cases and increased to 37 cases. The increasing cases of leprosy were allegedly caused by things associated with the incidence of leprosy in the district of Belu residential density, contact history and social-economy. Objective: To know the prevalence of pausibasilery and multibacillary leprosy building on the characteristic of residential density, contact history, social economy in Belu regency, Nusa Tenggara Timur Province. Methods: This research is a observational descriptive study with cross sectional design. The sampling technique used is Totality Sampling by univariate analysis. Results: Respondents leprosy Pausibasiler type as many as 23 (62.2%) and multibacillary type were 14 (37.8%). Respondents with residential density> 8m2 as many as 16 (43.2%) people, and respondents with residential density Rp. 925.000, while respondents with income